$\text{Đáp án+Giải thích các bước giải:}$
`a) 3x(x-1)+x-1=0 ⇔ 3x(x-1)+(x-1)=0`
`⇔ (3x+1)(x-1)=0 ⇔ x=1;-1/3`
`b) (x-2)(x²+2x+7)+2(x-2)(x+2)-5(x-2)=0`
`⇔ (x²+2x+7+2x+4-5)(x-2)=0`
`⇔ (x²+4x+6)(x-2)=0`
`Mà x²+4x+6=x²+4x+4+2≥2`
`⇒ x-2=0 ⇒ x=2`
`c) (2x-1)²-25=0`
`⇔ (2x-1-5)(2x-1+5)=0`
`⇔ (2x-6)(2x+4)=0`
`⇔ x=3;-2`
`d) x³+27+(x+3)(x-9)=0`
`⇔ (x+3)(x²-3x+9)+(x+3)(x-9)=0`
`⇔ (x+3)(x²-2x)=0`
`⇒ x=-3;0;2`
`e) 8x²-50x=0`
`⇔ 2x(4x-25)=0`
`⇔ x=0;x=25/4`
`f) 2(x+3)-x²-3x=0`
`⇔ 2(x+3)-(x²+3x)=0`
`⇔ 2(x+3)-x(x+3)=0`
`⇔ (2-x)(x+3)=0`
`⇔ x=2;-3`
`g) 6x²-15x-(2x-5)(2x+5)=0`
`⇔ 6x²-15x-4x²+25=0`
`⇔ 2x²-15x+25=0`
`⇔ 2(x²-7x/5+25/2)`
`⇔ 2(x-5)(x-5/2)=0`
`⇔ x=5;5/2`